Tuning the interfacial charge, orbital, and spin polarization properties in La0.67Sr0.33MnO3/La1-xSrxMnO3 bilayers - Carreira, Santiago José (2018)
The possibility of controlling the interfacial properties of artificial oxide heterostructures is still attracting researchers in the field of materials engineering. Here, we used surface sensitive techniques and high-resolution transmission electron microscopy to investigate the evolution of the surface spin-polarization and lattice strains across the interfaces between La0.66Sr0.33MnO3 thin films and low-doped manganites as capping layers. We have been able to fine tune the interfacial spin-polarization by changing the capping layer thickness and composition. The spin-polarization was found to be the highest at a critical capping thickness that depends on the Sr doping. We explain the non-trivial magnetic profile by the combined effect of two mechanisms: On the one hand, the extra carriers supplied by the low-doped manganites that tend to compensate the overdoped interface, favouring locally a ferromagnetic double-exchange coupling. On the other hand, the evolution from a tensile-strained structure of the inner layers to a compressed structure at the surface that changes gradually the orbital occupation and hybridization of the 3d-Mn orbitals, being detrimental for the spin polarization. The finding of an intrinsic spin-polarization at the A-site cation observed in x-ray magnetic circular dichroism (XMCD) measurements also reveals the existence of a complex magnetic configuration at the interface, different from the magnetic phases observed at the inner layers.